FRI0385 Non-Thrombotic Primary Antiphospholipid Kidney Disease, Longitudinal Follow up and Treatment Recomendations. (10th June 2014) - Olguin, L.; Alcala, M.; Cruz, C.
Abstract : Background: Renal disease associated with antiphospholipid syndrome has been studied for many years and vascular thrombotic lesions have predominantly been described. However, an expanding spectrum of renal diseases associated with APS has also been encountered and although "non-thrombotic" nephropaties have been reported, they are infrequent and poorly characterized. Objectives: To analyze the clinical and histological features of non-thrombotic kidney disease in a cohort of primary antiphospholipid syndrome (PAPS) patients and to propose treatment patterns besides anticoagulant therapy. Methods: From a dynamic cohort of 60 PAPS patients we identified 20 patients with decreased creatinine clearance (<60 ml/min) at least 2 times. All patients were receiving oral anticoagulation with a target INR 2-3, they underwent a renal function protocol which included: bimonthly creatinine clearance measurement, serum creatinine levels, urinalysis and arterial hypertension surveillance. If any of these parameters was abnormal, renal doppler, functional kidney scintigraphy and if possible, ultrasound-guided kidney biopsy was performed. After diagnosis of kidney disease, antihypertensives, mainly felodipine or enalapril were started regardless arterial hypertension. Patients have underwent follow-up for at least 12 months (range 14-136 months) Results: 20 patients (33%) from our cohort were identified. Demographic characteristics were: 5 male and15 female, mean age ± 38.6 years, mean disease duration 9.6 years. 8 patients had diastolic pressure >90 mmHg, the rest of them were normotensive. Median creatinine clearance was 46 ml/min ±8.3. Basal kidney scintigraphy reported diminished glomerular filtration rates in 16 patients. Renal Doppler was abnormal in 3 patients. Kidney biopsy was performed in 10 patients, histologic findings were: fibrous intimal thickening with luminal reduction in 9 cases, 18 patients had intimal hyperplasia, 18 biopsies reported mesangial hypercellularity, none of the renal specimens showed thrombosis or thrombotic mycroangiopathy. At follow up creatinine clearance raised to 79 ml/min ant month 4 and remains stable. Conclusions: The spectrum of PAPS renal disease is expanding and in patients under anticoagulant therapy with optimum INR, a new class of kidney disease without thrombotic findings but with some degree of diminished renal function sensitive to vasodilator drugs seems to be quite prevalent. Therefore we advise to follow up renal function regularly and to start vasodilators such as calcium channel blockers and/or angiotensin inhibitors. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5982